Using framing to foster creativity in learning: Reflective tool to analyze and discuss practice - Jónsdóttir, Svanborg Rannveig; Macdonald, Marey Allyson (Frontiers in Education, 2022)
Several models have been devised in Iceland in recent years to analyze emerging pedagogies in practice. In this article we present a model that was developed and tested in research on innovation and entrepreneurial education in 2011 and subsequently applied in two participatory action research (PAR) projects with teachers in Iceland both focusing on creativity. The model draws on sociological concepts from Basil Bernstein’s theories, such as “framing and classification” and “power and control” in school settings. Through multiple iterations, the model was converted into a practical analytical tool. The tool helps to reveal the range of elements that teachers can control or give students agency by applying different strengths of framing. When breaking down the elements we found that concepts such as freedom versus control can help to identify how these elements emerge and are applied in school practice and how they can support or hinder creativity. Working in the two PARs with subject teachers on four different school levels, we found out how the teachers used the tool to support their understanding of how to cultivate creativity in their students’ learning. We found that the tool is useful for teachers at any school level and in any subject to identify and understand which elements they control in teaching and learning processes and how they can support students’ creativity.